Perinatal asphyxia syndrome in the foal: review and a case report - Galvin Noreen; Collins Donald (Irish Veterinary Journal, 2004)
This report presented a brief overview of the literature on the perinatal asphyxia syndrome (PAS) in foals as a prelude to a description of the investigation and treatment of acute onset seizures in a 24-hour-old Thoroughbred colt foal. PAS can cause a wide variety of clinical abnormalities, of which seizures due to encephalopathy are the most significant. The structural and biochemical components of CNS neurones are disrupted by the shift from oxidative to anaerobic metabolism, with a resultant deficit in cellular energy. The cells succumb to the combined effects of acidosis, neurotoxic activities of glutamate, nitric oxide and free radicals, lipid peroxidation, accumulation of intracellular calcium and destructive overactivity of intracellular enzymes. Concurrently, the hypoxia affects other organ systems and management of foals presenting with CNS signs requires the veterinarian to undertake a thorough clinical examination and to institute appropriate therapy for the various derangements induced by the hypoxic-ischaemic episode. Diazepam (0.1 to 0.2 mg/kg bwt) can be used for short-term control of seizures; phenobarbital (2 to 10 mg/kg bwt) may be required for more prolonged treatment of recurrent seizures. The needs of the affected foal for nutrients, fluids and electrolytes, antimicrobial therapy and ancillary therapies were discussed in the literature review and illustrated in the case report.